Are we fearful of tubeless percutaneous nephrolithotomy? Assessing the need for tube drainage following percutaneous nephrolithotomy - Joel E Abbott; Samuel G Deem; Natalie Mosley; Gary Tan; Nathan Kumar; Julio G Davalos (Urology Annals, 2016)
Objective: The objective was to demonstrate that percutaneous nephrolithotomy (PCNL) can be safely performed with a tubeless or totally tubeless drainage technique. Introduction: Standard PCNL includes nephrostomy tube placement designed to drain the kidney and operative tract at the conclusion of the procedure. Modern technique trend is tubeless PCNL and totally tubeless PCNL, which are performed without standard nephrostomy drainage. We aim to reinforce current literature in demonstrating that PCNL can be safely performed using a tubeless technique. With compounded supportive data, we can help generate a trend toward a more cost-effective procedure with improved pain profiles and patient satisfaction, as previously shown with the tubeless technique. Methods: Retrospective analysis of 165 patients who underwent PCNL treatment was performed. Of this group, 127 patients underwent traditional nephrostomy drainage following PCNL. A tubeless procedure was performed in the remaining 38 patients. Patient's postoperative stone size and burden as well as complication profiles were analyzed. Largest stone size and total stone burden was similar between the groups. Results: Patient characteristics and demographic information were compared and no significant statistical difference was identified between the groups. Complication rates between the groups were compared and no statistical difference was noted. A total of 23 patients had at least one postoperative complication. Conclusion: Tubeless and totally tubeless PCNL demonstrates equivalent outcomes in the properly selected patient group when compared to PCNL performed with a nephrostomy tube. Although this is not the first study to demonstrate this, a large majority of urologists continue standard nephrostomy placement after PCNL. More studies are needed that demonstrate safety of this practice to shift the pendulum of care. Thus, tubeless and totally tubeless PCNL can be performed safely and effectively, which has previously been shown to improve cost, patient pain profiles, and length of hospitalization.